Physiotherapy Management of Down Syndrome: Case Report - Efendi, Alfina Ramadani Dyah; Naufal, Adnan Faris; Viola, Christine (Academic Physiotherapy Conference Proceeding, 2023)
Introduction : Down syndrome is a genetic condition or disorder caused by a chromosomal abnormality that occurs threefold in total or part of chromosome 21. Decreased muscle strength and balance are one of the consequences that occur in the condition of down syndrome. In this study the aim was to determine the effect of providing physiotherapy management in cases of Down syndrome. The research method used in this study was a case study involving a 4-year-old girl diagnosed with Down syndrome. Subjects were given physiotherapy interventions for 3 weeks with a frequency of 2 meetings a week. The interventions provided were walking on a textured catwalk, walking on an inclined plane, and jumping on a trampoline based on a stretch-shortening exercise. The examination given for this case is checking muscle strength using the manual muscle testing method and checking balance using the balance beam test. In this study, the results showed that there were changes in the subject's muscle strength and dynamic balance ability.